Reliability and benefits of clinical examination for determining the affected level in cervical compressive myelopathic patient: a prospective study of 44 cases - Chowdhury, Sharif Md Noman Khaled; Chowdhury, Forhad Hossain; Mirjada, Md Rashed; Haque, Md Raziul; Sarkar, Mainul Haque; Hossain, Sader (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: neurological examination; compressive myelopathy; MRI; myelomere; myelomelacia doi: 10.3329/jcmcta.v19i2.3864 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):12-15